Theological Reflections on the Oracles against the Nations - Chae, Moon Kwon (Horizons in biblical theology, 2015)
This paper illuminates the positive theological value of the oracles against the nations (oans) in the Old Testament. Tracing the historical development of the oan tradition, I propose that the oan tradition originated in a war or a cultic setting and went through three stages of transformation: first, the shift from salvation oracles for Israel to oracles against Israel by the 8th century prophets Amos and Isaiah: second, the shift from a realistic depiction of enemies to a more cosmic depiction of them during the exilic period: third, the inclusion of the nations into the future restoration in the postexilic period. The trajectory of the development of the oan tradition shows how Israel’s self-understanding and attitude toward foreign nations changed with a strong emphasis on Yahweh’s kingship. The emphasis on Yahweh’s kingship over Israel’s special status provides a ground for the inclusion of foreign nations into Yahweh’s plan. By prioritizing Yahweh’s kingship, his people can avoid the danger of self-elevation and embrace the other people into the community.